(3JMQjQ cJGH GdeSGcfs - (3KGhPhSjhSs
(3ChdgG (B:s
(3hdG jWdY Ydjge TF eeG jNai Yfge hdG HGdYcS adjcf aEf fUa ef MjK GdfXQ ai GdMQcI GdChdi s
(3BNQgG (B:s
(3Ef dfG ai GdfgGQGJ Edi djGdjgG cd SfI hPdc eG CQOfGg Je GdeSGcf dKGhPhSjhS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1458s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs